2020
DOI: 10.1021/acs.joc.0c00149
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3-Azabicyclo[m.2.0] Ring Systems via a Copper-Catalyzed Cascade Reaction of Diazo Compounds with 1,n-Allenynes

Abstract: A copper-catalyzed cascade reaction of diazo compounds with 1,n-allenynes (n = 6,7) was reported, which provides efficient access to various functionalized 3-azabicyclo­[m.2.0] frameworks (m = 5,6) in moderate to excellent yields under mild reaction conditions. The reaction proceeds through intermolecular cross-coupling to form bisallene intermediates, followed by subsequent intramolecular [2+2] cycloaddition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…N-Containing polycyclic compounds make up an important class for bioactive substances, natural products, and medicine . Construction of various polycyclic compounds through domino or cascade reactions is always an effective method, featuring a high efficiency, a simple process, and easy handling. However, the reaction systems are always complex, and multiple metals, noble ligands, and base or acid additives are required.…”
mentioning
confidence: 99%
“…N-Containing polycyclic compounds make up an important class for bioactive substances, natural products, and medicine . Construction of various polycyclic compounds through domino or cascade reactions is always an effective method, featuring a high efficiency, a simple process, and easy handling. However, the reaction systems are always complex, and multiple metals, noble ligands, and base or acid additives are required.…”
mentioning
confidence: 99%
“…To this end, 31 examples of functionalized 3‐azabicyclo[ m .2.0] ring systems 95 in moderate to excellent yields (up to 91%, Scheme 29) were obtained by the same research group. [ 111 ] The variations in N ‐protection and aliphatic linkers were investigated and showed that different aryl groups linked to sulfonyl functionality and the aliphatic linker bearing cyclohexane or a methyl or a phenyl group were well suitable for the protocol. Similar to their previous reports, [ 110 ] the bicyclization process was thought to proceed through a sequence that involved intermolecular cross‐coupling and intramolecular [2 + 2] cycloaddition.…”
Section: Synthesis Of Heterocyclesmentioning
confidence: 99%
“…Subsequently, our group further employed a similar strategy to develop a more general copper-catalyzed cascade reaction of -aryl--diazo esters 20 with 1,n-allenynes 94 for the rapid construction of various cyclobutane-fused bicyclo[m.2.0] (m = 5, 6) systems 95 (Scheme 29). 37 The reaction similarly proceeds via the formation of a bisallene intermediate followed by an intramolecular [2+2] cycloaddition. This protocol features mild reaction conditions, moderate to excellent yields, and a broad substrate scope.…”
Section: Short Review Synthesis 3 Cycloadditionmentioning
confidence: 99%